PEMBERDAYAAN EKONOMI KELUARGA MELALUI KELOMPOK PKK KELURAHAN KARANG PULE MATARAM - Tina Agustin; Yudi Pratomo; Angga Yunda (Yayasan Nusa Cendekia Global, 2025)
Pemberdayaan Kesejahteraan Keluarga or well known as PKK in the community is very important. PKK plays a role in empowering families in improving the welfare and family quality in aspects of health, morals, faith and behavior. An effort to improve the welfare of the family can be realized through pioneering Usaha Kecil Menengah (UKM). In practice, the implementation and development of UKM has some difficulties such as limited human resource skills and limited market information opportunities. This is experienced by many family groups, one of them is family groups in Karang Pule, Sekarbela. Here is the need for participation from the PKK Movement to help empower families in pioneering UKM in the form of skills training. This is inline with one of the main programs of PKK namely Education and Skills. On this occasion, as a form of community service, the authors cooperate with PKK Karang Pule order to improve family welfare in the local environment through the improvement of cooking skills that are expected to be useful later